Mushroom extract of Lactarius deliciosus (L.) Sf. Gray as biopesticide: Antifungal activity and toxicological analysis. Issue 2 (17th January 2022) - Volcão, Lisiane Martins; Halicki, Priscila Cristina Bartolomeu; Christ-Ribeiro, Anelise; Ramos, Daniela Fernandes; Badiale-Furlong, Eliana; Andreazza, Robson; Bernardi, Eduardo; da Silva Júnior, Flávio Manoel Rodrigues
ABSTRACT: Monilinia fructicola (Wint.) Honey is a plant pathogenic fungus that infects stone fruits such as peach, nectarine and plum, which are high demand cultivars found in Brazil. This pathogen may remain latent in the host, showing no apparent signs of disease, and consequently may spread to different countries. The aim of this study was to evaluate the activity of hydroalcoholic extract (HydE) obtained from Lactarius deliciosus (L.) Sf. Gray a mushroom, against M. fructicola phytopathogenic-induced mycelial growth. In addition, the purpose of this study was to examine phytotoxicity attributed to HydE using Brassica oleracea seeds, as well as cytotoxic analysis of this extract on cells of mouse BALB/c monocyte macrophage cell line (J774A.1 cell line) (ATCC TIB-67). The L. deliciosus HydE inhibited fungal growth and reduced phytopathogen mycelial development at a concentration of 1.25 mg/ml. Our results demonstrated that the extract exhibited phytotoxicity as evidenced by (1) interference on germination percentage and rate index, (2) decreased root and initial growth measures, and (3) lower fresh weight of seedlings but no cytotoxicity in Vero cell lines. Data suggest that the use of the L. deliciosus extracts may be beneficial for fungal control without any apparent adverse actions on mouse BALB/c monocyte macrophage cell line (J774A.1 cell line) viability.